Morphological, Physiological, and Structural Responses of Two Species of Artemisia to NaCl Stress - Zhi-Yong Guan; Yi-Ji Su; Nian-Jun Teng; Su-Mei Chen; Hai-Nan Sun; Chu-Ling Li; Fa-Di Chen (The Scientific World Journal)
Effects of salt stress on Artemisia scoparia and A. vulgaris “Variegate” were examined. A. scoparia leaves became withered under NaCl treatment, whereas A. vulgaris “Variegate” leaves were not remarkably affected. Chlorophyll content decreased in both species, with a higher reduction in A. scoparia. Contents of proline, MDA, soluble carbohydrate, and Na+ increased in both species under salt stress, but A. vulgaris “Variegate” had higher level of proline and soluble carbohydrate and lower level of MDA and Na+. The ratios of K+/Na+, Ca2+/Na+, and Mg2+/Na+ in A. vulgaris “Variegate” under NaCl stress were higher. Moreover, A. vulgaris “Variegate” had higher transport selectivity of K+/Na+ from root to stem, stem to middle mature leaves, and upper newly developed leaves than A. scoparia under NaCl stress. A. vulgaris “Variegate” chloroplast maintained its morphological integrity under NaCl stress, whereas A. scoparia chloroplast lost integrity. The results indicated that A. scoparia is more sensitive to salt stress than A. vulgaris “Variegate.” Salt tolerance is mainly related to the ability of regulating osmotic pressure through the accumulation of soluble carbohydrates and proline, and the gradient distribution of K+ between roots and leaves was also contributed to osmotic pressure adjustment and improvement of plant salt tolerance.